Violence against Women and Reproductive Health in Pakhribash Municipality - Pradhan, Niraj (Rupantaran: A Multidisciplinary Journal, 2023)
The United Nations defines that violence against women is any act of gender-based violence that results in, or is likely to result in, physical, sexual, or mental harm or suffering to women, including threats of such acts, coercion, or arbitrary deprivation of liberty, whether occurring in public or in private life. The main objective of the study was to find out the effects of violence against women. This paper was based on qualitative data using both the primary and secondary data sources. In this purpose the snow-ball sampling method was used to select the 110 victimized respondent women. In the study area, out of 110 women, all the women who had heard about women violence and higher number of women faced coercive sex during pregnancy period. All the women were facing health problem up to now because of the violence directed against them. It also makes the women to remain in the position of inferiority complex all these lead to women's reproductive health as well as well-being more vulnerable throughout the life.